Interference of the criminal procedure of Belarus with the jurisprudence of the European Court of Human Rights - Samaryn, Vadzim I. (Journal of the Belarusian State University. Law, 2022)
The article analyses a number of decisions of the European Court of Human Rights in order to give recommendations to the agencies of the Republic of Belarus conducting criminal proceedings on the formulation of procedural documents drawn up within the framework of the international legal assistance for the implementation of the tasks of criminal procedure in relation to ordinary crimes. It has been determined that the criminal procedure of Belarus interferes with the practice of the mentioned court in cases where a person believes that the decisions of officials of the host state (a member of the Council of Europe), adopted on the basis of a request from the agency of the Republic of Belarus conducting the criminal proceedings, may hypothetically lead to a violation of his rights protected by the Convention for the protection of human rights and fundamental freedoms. The conclusion formulates the legal positions of the European Court of Human Rights, which are important for achieving the effectiveness of the provision of international legal assistance in criminal matters to Belarus in relations with the member states of the Council of Europe.
Keywords: criminal procedure; international judicial protection; international legal assistance in criminal matters; international legal paradigm; European Court of Human Rights